Pemikiran Politik al-Shawkânî dalam Fath al-Qadîr - Hanafi, Yusuf (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2014)
Muhammad b. âAlÃ® Muhammad b. âAbd AllÃ¢h al-ShawkÃ¢nÃ® al-SanâÃ¢nÃ®. He was born in the Hijrah in ShawkÃ¢n village, Yemen on Monday 28 DhÃ» al-Qaâdah 1172 H and died on Tuesday, 27 JumÃ¢d al-AkhÃ®r 1250 H at the age about 78 years. Al-ShawkÃ¢nÃ® grew up in the Sanâa city, it is the capital of the republic of Yemen now. He study first time about religion from his father, then from renowed scholars in Sanâa and its surrounding, he was known as a scolar who mastered the various branches of religious sciences. Such as tafsÃ®r, hadÃ®th, fiqh, usÃ»l al-fiqh, history, science of kalÃ¢m, philosophy, balÃ¢ghah, mantiq etc. the main issue in this article is how political thought in the book of tafsir Fath al-QadÃ®r is the work of ShawkÃ¢nÃ®. At the end of article, the authors found that the intended political thinking in the study of Fath al-QadÃ®r is about constitutional ideas. These ideas about the constitution is limited to the concept of leadership and deliberation, the concept of the right of citizen to obtain justice, and the concept pf the right of citizens to live association and assembly